Does Transitioning to a Brace Improve HRQoL After Casting for Early Onset Scoliosis?. Issue 3 (9th March 2023) - Henstenburg, Jeffrey; Heard, Jeremy; Sturm, Peter; Blakemore, Laurel; Li, Ying; Ihnow, Stephanie B.; ,; Shah, Suken A.
Abstract : Background: Serial casting is favored for the initial treatment of early onset scoliosis (EOS), but there is concern about significant morbidity and caregiver burden. Studies have examined the utility of bracing as an alternative to casting, but little is known about differences in health-related quality of life (HRQoL) between treatments. We hypothesized that patients with a diagnosis of idiopathic EOS experience an improvement in HRQoL when transitioning from serial casting to bracing as measured by the 24-Item Early Onset Scoliosis Questionnaire (EOSQ). Methods: Subjects with idiopathic EOS were retrospectively identified from a multicenter database. EOSQ scores were compared before treatment, after index casting, after transition out of cast to brace, and at the most recent follow-up. Available major curve magnitudes were also compared during these time points. Data were compared using repeated-measures ANOVA with post hoc Bonferroni correction. Results: Sixty-six subjects met the inclusion criteria. Thirty-seven (56%) subjects were male and the average age at the time of index treatment was 1.9 (0.37-6.4) years. The average follow-up was 3.2 (0.90-6.8) years. In 57 subjects, the major curve magnitude improved from a mean of 33 (CI 28-37) degrees before treatment initiation to 27 (CI 23-30) degrees after casting and to 24 (CI 20-29) degrees at the most recent follow-up. The HRQoL subdomain showed a significant decrease in HRQoL during casting treatment 75.7 (CI 72.9-78.5) from pre-index treatment 84.9 (CI 81.4-88.5), during brace treatment 84.8 (CI 81.8-88.0) and at most recent follow-up 87.0 (CI 83.6-90.3) ( P <0.001). The parental impact subdomain improved from the beginning to the end of treatment (77.7 to 87.7, P =0.001) (n=64). Satisfaction improved from casting to bracing (73.4 to 86.7, P <0.001) (n=63) and to the most recent follow-up (73.4 to 87.9, P <0.001). Conclusion: Patients treated with casting for EOS experience reversible declines in HRQoL. After patients transition from casting to bracing, EOSQ scores recover to pretreatment baseline levels and are maintained at follow-up. This information must be balanced with the effectiveness of treatment for EOS with either method and customized for each patient. Level of Evidence: Level III—retrospective comparative study.